A vacuum water absorption construction technology for crack-proof and low-noise micro-surfacing
Through the vacuum water absorption construction process, the problem of severe dependence on climatic conditions and long forming time of microsurfaces is solved, and early open traffic and crack resistance is improved, noise is reduced and construction season is extended.
Patent Information
- Application Number
- CN202211634902.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-19
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2042-12-19
AI Technical Summary
The existing microsurface construction technology is highly dependent on climatic conditions, has a long forming time, and is very noisy, which affects the construction season and traffic opening time.
Adopt vacuum water absorption construction technology at the anti-crack type low-noise microsurface, including asphalt fiber sealing, mixing and spreading of slurry mixtures, vacuum water absorption, curing material spread and open traffic, gradually increase the vacuum degree through a vacuum pump to accelerate moisture absorption , shorten the forming time.
It extends the construction season, shortens the forming time, improves crack resistance and service life, and reduces noise without affecting the construction performance, and achieves early open traffic.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of asphalt pavement, in particular to a vacuum water absorption construction process for anti-cracking low-noise micro-surfacing. Background Art
[0002] Due to its outstanding advantages such as economy, high efficiency and speed, micro-surfacing has not only become the main maintenance method, but also has been widely used in highway engineering construction, and is often used for surfacing and filling ruts. Micro-surfacing is a process in which particles of different particle sizes are mixed into aggregates according to a proportional range, and the aggregates are then mixed with modified emulsified asphalt and water to form a modified emulsified asphalt slurry mixture (referred to as slurry mixture), which is quickly spread on the original road surface and cured (i.e., the process of water consumption, the existing technology relies on natural evaporation) to form a pavement structure layer. The single layer thickness of the coarsest MS-3 micro-surfacing is only about 1 cm. Due to its thin thickness, it is called micro-surfacing. The current specification calls MS-3 micro-surfacing a coarse micro-surfacing.
[0003] In single-layer micro-surfacing (which means the paving thickness is the same as the maximum aggregate crushed stone particle size), the aggregate maximum particle size crushed stone "stands upright" to form a strong skeleton structure, which will not produce rutting due to insufficient shear strength, but the anti-cracking performance is relatively weak. In addition, the driving noise of the micro-surfacing is relatively large. For this reason, the asphalt fiber layer anti-cracking waste tire rubber powder noise reduction micro-surfacing is invented. It uses emulsified asphalt to bond the fiber to the original road surface, and then makes a micro-surfacing mixed with waste tire rubber powder on it, and the surface structure layer is formed after maintenance.
[0004] At present, the formation time of micro-surfacing (i.e. the time it takes to open to traffic) is relatively long and is severely restricted by weather factors. Even if construction is carried out in fine weather from May to October, it generally takes 2h to 3h to open to traffic. If construction is carried out in lower temperatures or on cloudy and humid days, it will take several hours or even days to open to traffic. This shows that micro-surfacing has strict requirements on the climatic conditions for construction.
[0005] Since the asphalt fiber layer anti-cracking waste tire rubber powder noise reduction micro-surfacing uses more emulsified asphalt than ordinary micro-surfacing, its molding time is longer. Summary of the invention
[0006] The purpose of the present invention is to provide a vacuum water absorption construction process for crack-proof low-noise micro-surfacing, which reduces dependence on weather conditions, prolongs the construction season, speeds up the forming time of micro-surfacing, and enables early opening of traffic.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A vacuum water absorption construction process for crack-proof low-noise micro-surfacing includes the following steps:
[0009] The first step is to make asphalt fiber seal
[0010] Step 2: Slurry Mixing / Spreading
[0011] Follow the relevant provisions of (JTG F40-2004) "Technical Specifications for Highway Asphalt Pavement Construction";
[0012] Step 3: Vacuum water absorption
[0013] Start the vacuum pump, the vacuum degree in the slurry mixture gradually increases, and the water is sucked out. When the water absorption is normal, the vacuum degree is controlled at 0.08MPa. When no water can be sucked out, the vacuum degree is gradually increased to absorb water until the vacuum degree increases to 0.13MPa. When no water can be sucked out for 2 minutes, the water absorption is terminated;
[0014] Step 4: Maintenance II
[0015] Maintenance II is to spread the maintenance material, i.e. stone chips, to prevent the asphalt from sticking to the wheels;
[0016] Step 5: Opening up traffic
[0017] Traffic will be opened after the stone chips are spread.
[0018] Furthermore, the first step of making the asphalt fiber seal layer includes: spreading the first layer of emulsified asphalt, spreading the fibers, spreading the second layer of emulsified asphalt and curing I. The first layer of emulsified asphalt is used to bond the fibers to the original road surface, and the fibers play a role of reinforcement to improve the crack resistance of the road surface; the second layer of emulsified asphalt is used to bond the fibers to the micro-surface. Curing I is to spread the curing material, i.e., stone chips, which is used to prevent the asphalt from sticking to the wheels.
[0019] Furthermore, the asphalt used in the asphalt fiber seal layer is SBR modified emulsified asphalt.
[0020] Furthermore, the fiber used in the asphalt fiber seal layer is one or more mixtures of glass fiber, polyacrylonitrile fiber, polyester fiber, lignin fiber, mineral fiber and steel fiber, and the fiber length is controlled at 5 cm to 10 cm.
[0021] Furthermore, the specifications and quality of the materials used are in compliance with the requirements of (JTG F40-2004) Technical Specifications for Highway Asphalt Pavement Construction.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The construction process of the present invention can extend the construction season. Under the existing technical conditions, micro-surfacing is generally carried out in fine weather from May to October, and its forming speed is related to many climate factors such as sunlight intensity, temperature, humidity and wind speed; while the present invention can be constructed as long as it is not raining or icing, which extends the construction season.
[0024] 2. The present invention adopts vacuum water absorption to speed up the molding speed, and traffic can be opened after construction; while under the existing technical conditions, moisture depends on natural evaporation, and even if the micro-surfacing is constructed in sunny weather in summer, it takes 2h-3h to open traffic.
[0025] 3. In engineering practice, multi-layer micro-surfacing is used to fill deep ruts (ruts with a depth greater than 1 cm). In order to improve the anti-rutting performance of multi-layer micro-surfacing, SBS modified emulsified asphalt is developed and utilized, but the filling body still produces ruts again. The contribution rate of bonding force to the shear strength of asphalt pavement is much lower than the friction force within the aggregate. It is wrong to ensure the shear strength of asphalt pavement by increasing the softening point of asphalt binder. The right way is to improve the skeleton efficiency of aggregate. Filling ruts with a slurry mixture with a maximum aggregate crushed stone particle size equal to the rut depth can ensure that the filling body will not produce ruts again. Therefore, ultra-coarse micro-surfacing (referring to the surface formed by paving with an emulsified asphalt slurry mixture with a maximum aggregate crushed stone particle size exceeding 1 cm, that is, the single layer thickness exceeds 1 cm) has been developed. Its forming speed is very slow. For example, a 3cm thick ultra-coarse micro-surfacing takes 3d to 5d to form even in continuous sunny weather in summer. The vacuum water absorption construction technology of the present invention can achieve the effect of opening traffic after construction.
[0026] 4. In the slurry mixture, water first forms a water film on the surface of the aggregate, and then the emulsified asphalt breaks, and then an asphalt film is gradually formed outside the water film, which greatly reduces the bonding force between the asphalt and the aggregate. Under the condition of natural volatilization, the moisture wrapped by the asphalt film cannot be volatilized for a long time, resulting in a shortened service life of the micro-surface. The vacuum water absorption construction technology of the present invention can absorb most of the moisture wrapped by the asphalt film, reducing the adverse effect of moisture on the bonding force between asphalt and aggregate, which is beneficial to improving the service life of the micro-surface. DETAILED DESCRIPTION
[0027] The technical solutions and effects of the present invention are further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0028] Example 1
[0029] For example, in December when there is no rain or ice, anti-crack low-noise MS-3 micro-surfacing construction is carried out, and the paving box width (referring to the width of the slurry mixture paving) is 3m. The specific method is as follows:
[0030] 1. Design the material dosage and slurry mixture proportion before construction.
[0031] The quality of the materials used meets the requirements of (JTG F40-2004) "Technical Specifications for Highway Asphalt Pavement Construction".
[0032] 1. Amount of asphalt fiber seal material
[0033] The amount of emulsified asphalt to be spread in the first layer is (0.3~0.7) kg / m 2 In this embodiment, 0.5 kg / m 2 .
[0034] The fiber can be glass fiber, polyacrylonitrile fiber, polyester fiber, lignin fiber, mineral fiber and steel fiber, or a mixture of several thereof. The fiber length is controlled at 5cm~10cm, and the fiber layer dosage is (80~160)g / m 2 In this embodiment, glass fiber is used, and the amount is 120g / 1000m 2 .
[0035] The second layer of emulsified asphalt is (0.3~0.7) kg / m 2 In this embodiment, 0.5 kg / m 2 .
[0036] Maintenance I is to spread the maintenance material, i.e. stone chips, with a dosage of (1.5~2)m 3 / 1000m 2 , in this embodiment, 1.5m 3 / 1000m 2 . The stone chips should be spread evenly.
[0037] Asphalt fiber seal not only improves the anti-cracking performance of the micro surface, but also improves the anti-cracking performance of the entire pavement.
[0038] 2. Slurry mixture proportion design
[0039] The slurry mixture includes stone aggregate, waste tire rubber powder, SBR modified emulsified asphalt, water, and additives. The aggregate includes stone aggregate and waste tire rubber powder, of which:
[0040] The grading of stone aggregate is as follows: the mass of aggregate with a particle size of no more than 9.5mm accounts for 100% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 4.75mm accounts for 70%~90% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 2.36mm accounts for 45%~70% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 1.18mm accounts for 28%~50% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 0.6mm accounts for 19%~34% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 0.3mm accounts for 12%~25% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 0.15mm accounts for 7%~18% of the total mass of aggregate; the mass of aggregate with a particle size of no more than 0.075mm accounts for 5%~15% of the total mass of aggregate;
[0041] The powder-aggregate ratio is 1.5%~3%. The powder-aggregate ratio is the ratio of the mass of waste tire rubber powder to the total mass of aggregate. The internal mixing method is adopted to replace the same mass of aggregate with a particle size not greater than 1.18mm with the same mass of waste tire rubber powder. The waste tire rubber powder is used as part of the aggregate. The use of waste tire rubber powder can reduce driving noise by 3dB~5dB, which is equivalent to reducing the traffic volume by half, or doubling the distance away from the noise source.
[0042] The oil-to-stone ratio is 7% to 10%, which is the ratio of the mass of the evaporation residue of the modified emulsified asphalt to the total mass of the aggregate;
[0043] The water-to-aggregate ratio is 4% to 10%. The water-to-aggregate ratio is the ratio of the total water mass to the total aggregate mass. The total water mass refers to the sum of the water mass contained in the modified emulsified asphalt and the added water mass.
[0044] Additives are determined as needed, and the additives are slaked lime or cement.
[0045] The specific steps of slurry mixture proportion design are as follows:
[0046] 1) Configure optimized aggregate gradation.
[0047] According to the gradation of stone aggregate, the optimized mass proportion of various aggregates is determined, that is, the ratio of 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm crushed stone: stone chips: mineral powder; when the powder-aggregate ratio is selected, a larger powder-aggregate ratio should be selected when the gradation of stone aggregate is fine, and a smaller powder-aggregate ratio should be selected when the gradation of stone aggregate is coarse. The particle size of waste tire rubber powder is 20 mesh~30 mesh, which is 0.6mm~0.8mm when converted into millimeters. The same mass of waste tire rubber powder is used to replace the same mass of 0. 6mm~1.18mm stone aggregate, that is, using equal mass of waste tire rubber powder to replace stone chips. The grading ratio of aggregate will change after replacement, but this change is very small and does not affect the construction performance and road performance of the slurry mixture, so it can be ignored. After the amount of waste tire rubber powder is determined, the mass mix ratio of aggregate can be determined, that is, the ratio of 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm crushed stone: stone chips: waste tire rubber powder: mineral powder. During construction, the aggregate should be mixed according to the above ratio.
[0048] According to the design specifications, the total weight of aggregate used in the aggregate quality mix design is 100kg, of which the amount of stone with a particle size of 4.75mm~9.5mm is 25kg, the amount of stone with a particle size of 2.36mm~4.75mm is 25kg, the amount of stone chips is 45kg, and the amount of mineral powder is 5kg. The gradation of stone aggregate is: the aggregate with a particle size not greater than 9.5mm accounts for 100% of the total mass of aggregate; the aggregate with a particle size not greater than 4.75mm accounts for 75%; aggregates with a particle size of no more than 2.36mm account for 50% of the total mass of aggregates; aggregates with a particle size of no more than 1.18mm account for 30% of the total mass of aggregates; aggregates with a particle size of no more than 0.6mm account for 25% of the total mass of aggregates; aggregates with a particle size of no more than 0.3mm account for 15% of the total mass of aggregates; aggregates with a particle size of no more than 0.15mm account for 10% of the total mass of aggregates; aggregates with a particle size of no more than 0.075mm account for 7% of the total mass of aggregates. This gradation meets the requirements, therefore, the mix ratio of stone aggregates in this embodiment is: 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm rice stone: stone chips: mineral powder = 25:25:45:5.
[0049] If the powder-aggregate ratio is selected as 2%, the amount of waste tire rubber powder is: 100kg×2%=2kg; if 2kg of waste tire rubber powder is used to replace stone chips, the amount of stone chips is: 45kg-2kg=43kg. Then, the mix ratio of aggregates in this embodiment is: 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm rice stone: stone chips: waste tire rubber powder: mineral powder = 25:25:43:2:5.
[0050] 2) Configure optimized oil-stone ratio.
[0051] During implementation, the optional range of the asphalt-to-stone ratio is determined based on (T0752-2011) "Wet Wheel Abrasion Test for Slurry Mixtures" and (T0755-2011) "Load Wheel Adhesion Test for Slurry Mixtures". The minimum value is determined by (T0752-2011) "Wet Wheel Abrasion Test for Slurry Mixtures", and the maximum value is determined by (T0755-2011) "Load Wheel Adhesion Test for Slurry Mixtures". Then, an asphalt-to-stone ratio is determined based on experience. After the asphalt-to-stone ratio is determined, the amount of modified emulsified asphalt is calculated based on the content of evaporation residue in the modified emulsified asphalt.
[0052] The oil-stone ratio range determined by the wet wheel wear test and the load wheel sand adhesion test is: 7.5%~8.6%, and the oil-stone ratio is set to: 8%; then the amount of evaporation residue is: 8%×100kg=8kg, and the amount of modified emulsified asphalt in this embodiment is: 8kg÷60%≈13.3kg.
[0053] 3) Configure optimized additional water consumption.
[0054] During implementation, the amount of additional water is determined based on (T0751-1993) "Emulsified Asphalt Slurry Seal Mixture Consistency Test"; the consistency of the slurry mixture is required to be controlled between 2cm and 3cm to determine the amount of additional water.
[0055] The consistency test of the slurry mixture was conducted, and the requirement was met when the water-to-mass ratio was 8%. The total water consumption of this embodiment is: 8%×100kg=8kg, and the amount of additional water is: 8kg-13.3kg×(1-60%)≈2.7kg.
[0056] 4) Configure optimized mixing time.
[0057] According to (T0757-2011) "Mixing Test of Slurry Mixture", the mixing time of the slurry mixture shall be tested; the mixing time shall not be less than 120s; if the mixing time cannot meet the requirements, additives can be used to adjust it, and the dosage of the additives can be determined through tests. Additives are not required and are only used when the mixing time cannot meet the requirements.
[0058] The above method can determine the mix ratio of modified emulsified asphalt waste tire rubber powder slurry mixture, that is, the ratio of aggregate: modified emulsified asphalt: added water: additive (as needed), which is the basis for adjusting various material control systems of the slurry sealer.
[0059] The slurry mixture mixing test was carried out. The mixing time of this embodiment was 140s, which was greater than 120s and met the requirements, indicating that no additives were needed.
[0060] The result of the slurry mixture ratio of this embodiment is obtained through the above design, that is, the ratio of the modified emulsified asphalt waste tire rubber powder slurry mixture is: aggregate: modified emulsified asphalt: added water = 100:13.3:2.7, wherein the ratio of aggregate is: 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm rice stone: stone chips: waste tire rubber powder: mineral powder = 25:25:43:2:5.
[0061] 5) Check the workability of the slurry mixture
[0062] The key to the success of micro-surfacing construction lies in the workability of the slurry mixture. The goal pursued through the slurry mixture proportion design is the best workability, and the workability of the slurry mixture is tested through trial mixing and trial paving. The best workability is a comprehensive indicator that characterizes the construction performance of the modified emulsified asphalt slurry mixture. It means that the consistency of the slurry mixture is the best, that is, between 2cm and 3cm, the mixing time is greater than 120s, and the fluidity, plasticity, stability, uniformity, water retention and compactness are all good, that is, the best comprehensive performance that is conducive to the smooth progress of construction. These are the standards for testing whether the workability of the slurry mixture has reached the best.
[0063] 3. Amount of materials used for maintenance II.
[0064] Maintenance II is to spread the maintenance material, i.e. stone chips, with a dosage of (1.5~2)m 3 / 1000m 2 , in this embodiment, 1.5m 3 / 1000m 2 . The stone chips should be spread evenly.
[0065] 2. A vacuum water absorption construction process for anti-cracking low-noise micro-surface, comprising the following steps:
[0066] 1. According to 0.5kg / m 2 Spread the first layer of emulsified asphalt in the amount of.
[0067] 2. According to 120g / m 2 Sprinkle glass fiber in an appropriate amount.
[0068] 3. According to 0.5kg / m 2 Spread the second layer of emulsified asphalt in the amount of.
[0069] 4. Maintenance I. Maintenance I is to spread the maintenance material, i.e. stone chips, in an amount of 1.5m 3 / 1000m 2 Spread the stone chips evenly.
[0070] 5. Mixing / spreading of slurry mixture.
[0071] 1) Mix the aggregates according to the following proportion: 4.75mm~9.5mm crushed stone: 2.36mm~4.75mm rice stone: stone chips: waste tire rubber powder: mineral powder = 25:25:43:2:5, and mix evenly.
[0072] 2) The mixing / spreading of slurry mixture shall be carried out in accordance with the relevant provisions of (JTG F40-2004) "Technical Specifications for Highway Asphalt Pavement Construction".
[0073] 6. Vacuum water absorption.
[0074] Vacuum dehydration starts 15 minutes after the slurry mixture is spread, that is, after the slurry mixture is demulsified.
[0075] Start the vacuum pump to gradually increase the vacuum degree in the slurry mixture to absorb water. When water absorption is normal, the vacuum degree is controlled at 0.08MPa. When no water can be absorbed, the vacuum degree is gradually increased to absorb water until the vacuum degree increases to 0.13MPa. When no water can be absorbed for 2 minutes, the water absorption is terminated.
[0076] The vacuum water absorption equipment includes: vacuum water absorption filter cloth, vacuum water absorption pad, vacuum water absorption pipe and vacuum pump, wherein the vacuum water absorption filter cloth is laid on the paved slurry mixture, and the vacuum water absorption pad is laid on it, and the vacuum water absorption pad is connected to the vacuum pump through the vacuum water absorption pipe, and the vacuum pump is turned on to suck out the water generated after the emulsified asphalt is demulsified. When the vacuum water absorption pad is laid, the emulsified asphalt cement slurry with a thickness of 5mm and a width of 30mm~50mm is filled around and between the road surface, and is pressed and sealed; the emulsified asphalt cement slurry is made by mixing cement and emulsified asphalt, and its consistency requirement is 0.5cm~1cm, and the embodiment is 0.6cm. Among them: the size of the vacuum water-absorbing filter cloth is 3.1m×20m, the size of the vacuum water-absorbing pad is 3.2m×20.2m, the width of the paving box, vacuum water-absorbing filter cloth and vacuum water-absorbing pad are at least 10cm wide, and the length of the vacuum water-absorbing filter cloth and vacuum water-absorbing pad are at least 20cm long. Their length can be adjusted based on the principle of construction convenience.
[0077] After vacuuming is completed, remove the emulsified asphalt cement slurry.
[0078] Research shows that the forming time of micro-surfacing is directly related to the moisture content in the paved slurry mixture, that is, it is directly related to the speed of water consumption. The faster the water consumption, the shorter the time to open to traffic, and vice versa. Research shows that when the total water content in the slurry mixture (the sum of the added water and the water generated after the emulsified asphalt is demulsified) is consumed by 70% to 80%, the conditions for opening to traffic are met. Through vacuum water absorption, the total water content can be absorbed by more than 90%, so traffic can be opened after vacuum water absorption.
[0079] 7. Maintenance II.
[0080] Maintenance II is to spread the maintenance material, i.e. stone chips, in an amount of 1.5m 3 / 1000m 2 . The stone chips should be spread evenly.
[0081] 8. Open traffic.
[0082] Traffic will be opened after the stone chips are spread.
[0083] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A vacuum water absorption construction process for increasing the service life of micro-surfacing, characterized in that: The construction process The following steps are involved: The first step is to make asphalt fiber seal Step 2: Slurry Mixing / Spreading Step 3: Vacuum water absorption Step 4: Maintenance II Maintenance II is to spread the maintenance material, i.e. stone chips; Step 5: Opening up traffic Traffic will be opened after the stone chips are spread; Vacuum water absorption starts after the slurry mixture breaks. Start the vacuum pump, the vacuum degree in the slurry mixture gradually increases, and the water is sucked out. When the water absorption is normal, the vacuum degree is controlled at 0.08MPa. When no water can be sucked out, the vacuum degree is gradually increased to absorb water until the vacuum degree increases to 0.13MPa. When no water can be sucked out for 2 minutes, the water absorption is terminated. The vacuum water absorption equipment includes: vacuum water absorption filter cloth, vacuum water absorption pad, vacuum water absorption pipe and vacuum pump, wherein the vacuum water absorption filter cloth is laid on the paved slurry mixture, and the vacuum water absorption pad is laid on it, and the vacuum water absorption pad is connected to the vacuum pump through the vacuum water absorption pipe, and the vacuum pump is turned on to suck out the water generated after the emulsified asphalt is demulsified. When the vacuum water absorption pad is laid, the emulsified asphalt cement slurry with a thickness of 5mm and a width of 30mm~50mm is filled around and between the road surface, and is pressed and sealed; the emulsified asphalt cement slurry is made by mixing cement and emulsified asphalt, and its consistency is required to be 0.5cm~1cm, the size of the vacuum water absorption filter cloth is 3.1m×20m, the size of the vacuum water absorption pad is 3.2m×20.2m, the width of the paving box, the vacuum water absorption filter cloth and the vacuum water absorption pad is at least 10cm wide, and the length of the vacuum water absorption filter cloth and the vacuum water absorption pad is at least 20cm long; after the vacuum water absorption is completed, the emulsified asphalt cement slurry is removed; The first step of making the asphalt fiber seal layer includes: spreading a first layer of emulsified asphalt, spreading fibers, spreading a second layer of emulsified asphalt and curing I; The maintenance I is to spread the maintenance material, i.e. stone chips; The asphalt used in the asphalt fiber seal layer is SBR modified emulsified asphalt; The fibers used in the asphalt fiber seal are one or more mixtures of glass fibers, polyacrylonitrile fibers, polyester fibers, lignin fibers, mineral fibers and steel fibers, and the fiber length is controlled to be 5 cm to 10 cm.
Citation Information
Patent Citations
Asphalt fiber-enhanced waste tire rubber powder noise-reducing micro-surfacing structure layer and construction method thereof
CN104911975A
Static lossless granulation system for waste asphalt pavement
CN209631376U